2020
DOI: 10.3390/biom10040545
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor Erlotinib Induces Dry Skin via Decreased in Aquaporin-3 Expression

Abstract: An adverse reaction of dry skin occurs frequently during treatment with anticancer epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs). In this study, we conducted basic research to clarify the mechanism of EGFR-TKI-induced dry skin and propose new treatments or preventative measures. Dermal water content was significantly lower in the erlotinib-treated mice than in the control group. An assessment of the expression levels of functional genes in the skin revealed that only the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In addition, cutaneous AQP3 is known to change in various skin disorders [25]; for example, AQP3 is decreased in psoriasis [26] and vitiligo [27,28] and during aging [29], causing skin dryness. Furthermore, it was recently found that a decrease in skin AQP3 was involved in the dry skin observed upon treatment with an epidermal growth factor receptor (EGFR) inhibitor [30]. Therefore, xeroderma during type 2 diabetes may occur as a result of a decrease in cutaneous AQP3, which limits the movement of water from the vascular side of the skin to the stratum corneum, as observed in type 1 diabetes [8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cutaneous AQP3 is known to change in various skin disorders [25]; for example, AQP3 is decreased in psoriasis [26] and vitiligo [27,28] and during aging [29], causing skin dryness. Furthermore, it was recently found that a decrease in skin AQP3 was involved in the dry skin observed upon treatment with an epidermal growth factor receptor (EGFR) inhibitor [30]. Therefore, xeroderma during type 2 diabetes may occur as a result of a decrease in cutaneous AQP3, which limits the movement of water from the vascular side of the skin to the stratum corneum, as observed in type 1 diabetes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous AQP3 levels are also decreased at the onset of diabetes mellitus [ 23 , 39 ], vitiligo [ 40 , 41 ], and psoriasis [ 42 ], in which dry skin is observed. Moreover, skin disorders such as dry skin caused by epidermal growth factor receptor inhibitor administration may also be associated with decreased skin expression of AQP3 [ 24 ]. Thus, AQP3 is considered to be a key molecule that plays important roles in wound healing and skin moisturization.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared from mouse skin and HaCaT cells for western blotting in the same manner as previously reported [ 23 , 24 ]. The protein concentration was measured by the bicinchoninic acid method using bovine serum albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that the AQP3 level in the skin decreases when the skin dries due to psoriasis [ 22 ], vitiligo [ 23 , 24 ], diabetes mellitus [ 25 ], aging [ 26 ], and anti-cancer drugs [ 27 ]. This result suggests that the increased AQP3 expression in the skin is associated with the increase in skin moisture by astaxanthin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, research has clarified that the AQP3 level in the skin decreases when the skin dries due to psoriasis [ 22 ], vitiligo [ 23 , 24 ], diabetes mellitus [ 25 ], aging [ 26 ], etc. We previously confirmed that the dry skin that occurs with the administration of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors as anticancer agents is associated with decreased AQP3 levels in the skin [ 27 ]. Therefore, AQP3 is considered to play important roles in maintaining skin moisture and skin function.…”
Section: Introductionmentioning
confidence: 99%